MiR-153 Regulates Amelogenesis by Targeting Endocytotic and Endosomal/lysosomal Pathways–Novel Insight into the Origins of Enamel Pathologies - Yin, Kaifeng (Sci Rep, 2017)
Amelogenesis imperfecta (AI) is group of inherited disorders resulting in enamel pathologies. The involvement of epigenetic regulation in the pathogenesis of AI is yet to be clarified due to a lack of knowledge about amelogenesis. Our previous genome-wide microRNA and mRNA transcriptome analyses suggest a key role for miR-153 in endosome/lysosome-related pathways during amelogenesis. Here we show that miR-153 is significantly downregulated in maturation ameloblasts compared with secretory ameloblasts. Within ameloblast-like cells, upregulation of miR-153 results in the downregulation of its predicted targets including Cltc, Lamp1, Clcn4 and Slc4a4, and a number of miRNAs implicated in endocytotic pathways. Luciferase reporter assays confirmed the predicted interactions between miR-153 and the 3′-UTRs of Cltc, Lamp1 (in a prior study), Clcn4 and Slc4a4. In an enamel protein intake assay, enamel cells transfected with miR-153 show a decreased ability to endocytose enamel proteins. Finally, microinjection of miR-153 in the region of mouse first mandibular molar at postnatal day 8 (PN8) induced AI-like pathologies when the enamel development reached maturity (PN12). In conclusion, miR-153 regulates maturation-stage amelogenesis by targeting key genes involved in the endocytotic and endosomal/lysosomal pathways, and disruption of miR-153 expression is a potential candidate etiologic factor contributing to the occurrence of AI.